2020
DOI: 10.3390/jcm9092945
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Analysis of Saliva to Identify Oral Diseases Using a Point-of-Care Compatible qPCR Assay

Abstract: Oral health is maintained by a healthy microbiome, which can be monitored by state-of-the art diagnostics. Therefore, this study evaluated the presence and quantity of ten oral disease-associated taxa (P. gingivalis, T. forsythia, T. denticola, F. nucleatum, C. rectus, P. intermedia, A. actinomycetemcomitans, S. mutans, S. sobrinus, oral associated Lactobacilli) in saliva and their clinical status association in 214 individuals. Upon clinical examination, study subjects were grouped into healthy, caries and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…2016-00435, date of approval: 09.01.2016). A total of 120 subjects ( Figure 1 ) were asked to participate in a previous study (minimum age of 18 years; mean, 35.8 years; 57 females) and donate saliva for a microbial analysis and identification of diseases with a qPCR (quantitative polymerase chain reaction) assay [ 12 ]. Out of this cohort, stored (−80 °C, not longer than six months) saliva was used from healthy subjects ( n = 29; mean age, 31.8; 18 females), patients with gingivitis ( n = 22; mean age, 35.4; 13 females), and patients with open caries lesions ( n = 69; mean age, 37.6; 26 females).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2016-00435, date of approval: 09.01.2016). A total of 120 subjects ( Figure 1 ) were asked to participate in a previous study (minimum age of 18 years; mean, 35.8 years; 57 females) and donate saliva for a microbial analysis and identification of diseases with a qPCR (quantitative polymerase chain reaction) assay [ 12 ]. Out of this cohort, stored (−80 °C, not longer than six months) saliva was used from healthy subjects ( n = 29; mean age, 31.8; 18 females), patients with gingivitis ( n = 22; mean age, 35.4; 13 females), and patients with open caries lesions ( n = 69; mean age, 37.6; 26 females).…”
Section: Methodsmentioning
confidence: 99%
“…Progressing caries lesions cause an inflammation of the pulp, which leads to pulpitis and periapical periodontitis. Some bacteria, such as Streptococci and Lactobacilli , are particularly associated with the development of these caries lesions [ 2 , 12 ]. Persisting biofilms around the teeth on the gingival sulcus can also induce gingivitis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detection specificity to the selected resistance genes derives from the corresponding primers and potential probes. TaqMan or SYBR Green quantitative PCR assays are suitable, as they allow the monitoring of several genes of interest simultaneously [ 32 , 33 ]. The development of these assays is typically done in a buffer matrix, in order to avoid inhibitors for the assessment of the assay limit of detection.…”
Section: Designing Abr Screening Methods For Poc Dental Applicatiomentioning
confidence: 99%
“…Morozumi et al evaluated the amount of bacteria in saliva and IgG titers in serum to monitor the progression of chronic periodontitis (Morozumi et al, 2016). Paque et al recently reported that the strongest differences in eight bacterial targets (C. rectus, T. forsythia, P. gingivalis, S. mutans, F. nucleatum, T. denticola, P. intermedia, and oral Lactobacilli) were found between healthy controls and periodontitis patients by their newly developed qPCR analysis of saliva (Paque et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Paque et al. recently reported that the strongest differences in eight bacterial targets ( C. rectus , T. forsythia , P. gingivalis , S. mutans , F. nucleatum , T. denticola , P. intermedia , and oral Lactobacilli ) were found between healthy controls and periodontitis patients by their newly developed qPCR analysis of saliva ( Paque et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%